Thermoregulation is not impaired in breast cancer survivors during moderate‐intensity exercise performed in warm and hot environments - Relf, Rebecca L. (Physiol Rep, 2021)
This study aimed to assess how female breast cancer survivors (BCS) respond physiologically, hematologically, and perceptually to exercise under heat stress compared to females with no history of breast cancer (CON). Twenty‐one females (9 BCS and 12 CON [age; 54 ± 7 years, stature; 167 ± 6 cm, body mass; 68.1 ± 7.62 kg, and body fat; 30.9 ± 3.8%]) completed a warm (25℃, 50% relative humidity, RH) and hot (35℃, 50%RH) trial in a repeated‐measures crossover design. Trials consisted of 30 min of rest, 30 min of walking at 4 metabolic equivalents, and a 6‐minute walk test (6MWT). Physiological measurements (core temperature (T (re)), skin temperature (T (skin)), heart rate (HR), and sweat analysis) and perceptual rating scales (ratings of perceived exertion, thermal sensation [whole body and localized], and thermal comfort) were taken at 5‐ and 10‐min intervals throughout, respectively. Venous blood samples were taken before and after to assess; IL‐6, IL‐10, CRP, IFN‐γ, and TGF‐β(1). All physiological markers were higher during the 35 versus 25℃ trial; T (re) (~0.25℃, p = 0.002), T (skin) (~3.8℃, p < 0.001), HR (~12 beats·min(−1), p = 0.023), and whole‐body sweat rate (~0.4 L·hr(−1), p < 0.001), with no difference observed between groups in either condition (p > 0.05). Both groups covered a greater 6MWT distance in 25 versus 35℃ (by ~200 m; p = 0.003). Nevertheless, the control group covered more distance than BCS, regardless of environmental temperature (by ~400 m, p = 0.03). Thermoregulation was not disadvantaged in BCS compared to controls during moderate‐intensity exercise under heat stress. However, self‐paced exercise performance was reduced for BCS regardless of environmental temperature.